Morphometric study on knee parameters values derived from magnetic resonance imaging scan data of patients with knee injuries - Zulkaflee, Mohd Hazim (2016)
Knee joint is one of the important structures responsible for human locomotion and the commonest joint to suffer from injury in younger population who are active in sports. This problem is attributed to the complexity of knee joint structures as well as due to high degree of trauma inflicted by the injury. Magnetic resonance imaging (MRI) has been acknowledged as the superior modality used to diagnose cases of knee injury owing to its ability in demonstrating clear anatomical configuration of knee joint. A retrospective study was done on knee parameters values data derived from MRI scan images of knee joint obtained from Picture Archiving and Communication System (PACS) Database System of Hospital USM. Seventy four images were selected for morphometric analysis. The data were analyzed to determine the mean intercondylar notch width (ICW), mean length of posterior cruciate ligament (PCL), types of intercondylarnotch shape, relationship between ICW and PCL length, difference in PCL length between types of intercondylar notch shape and to compare ICW, PCL length, types of intercondylar notch shape, bicondylar width (BW) and notch width index (NWI) parameters between PCL-injured and non-PCL-injured groups of patients. Demographic data of the MRI scan images revealed higher mean value of ICW and PCL length in male than female patients [ICW: 22.3 (2.48), 19.5 (1.71) in male/female and PCL length: 39.8 (4.00), 35.9 (3.24) in male/female respectively]. Type A intercondylar notch has highest frequency based on gender and race factors [gender: type A = 55%, other type = 45% / race: type A = 55%, other type = 45%]. Significant relationship was found between ICW and PCL length with p<0.01. No significant difference was found in PCL length between types of intercondylar notch shape with p>0.0167. The comparison of knee parameters values between PCL-injured and non-PCL-injured groups of patients revealed that only PCL length was different between the groups with p<0.05. No significant association was found between types of intercondylar notch shape and PCL injury status with p>0.05. The findings might be beneficial to physicians and surgeons involved in assessment and management of PCL injury cases.